Cervical and intracranial artery dissections. (August 2021) - Engelter, Stefan T.; Lyrer, Philippe; Traenka, Christopher
This review summarizes recent therapeutic advances in cervical (CeAD) and intracranial artery dissection (IAD) research. Despite unproven benefits, but in the absence of any signal of harm, in patients, with acute ischemic stroke attributable to CeAD, intravenous thrombolysis and, in case of large-vessel occlusion, endovascular revascularization should be considered. Future research will clarify which patients benefit most from either treatment modality. For stroke prevention, the recently published randomized controlled TREAT-CAD study showed that, against the initial hypothesis, aspirin was not shown non-inferior to anticoagulation with vitamin K antagonists (VKAs). With the results of two randomized controlled trials (CADISS and TREAT-CAD) available now, the evidence to consider aspirin as the standard therapy of CeAD is weak. Further analyses might clarify whether the assumption supports, in particular, that patients presenting with cerebral ischemia, clinical or subclinical with magnetic resonance imaging surrogates, might benefit most from VKA treatment. In turn, it remains to be shown, whether in CeAD patients presenting with pure local symptoms and without hemodynamic compromise, antiplatelets are sufficient, and whether a dual antiplatelet therapy during the first weeks of treatment is recommendable. The observation that ischemic strokes occurred (or recurred) very early after CeAD diagnosis, consistently across randomized and observational studies, supports the recommendation to start antithrombotic treatment immediately, whatever antithrombotic agent is chosen in each individual case. The lack of a license for the use in CeAD patients and the paucity of data are still arguments against the use of direct oral anticoagulants in CeAD. Nevertheless, due to their beneficial safety and efficacy profile proven in atrial fibrillation, these agents are a worthwhile treatment option to be tested in further CeAD treatment trials. In IAD, the experience with the use of antithrombotic agents is limited. As the risk of suffering intracranial hemorrhage is higher in IAD than in CeAD, the use of antithrombotic therapy in IAD remains controversial.